Research on community-based mental health services for children and adolescents - Fisher, William H. (Oxford, UK : Elsevier JAI, 2007)
Research on mental health services for children and adolescents has become a vibrant subspecialty within the larger field of mental health services research. This research program experienced a somewhat later start than that focusing on adults, and faces a set of issues and challenges that are both different and in many ways more complex. The served population itself is bounded by infancy and the late teen years, and includes all age groups in between. This developmental spectrum naturally necessitates there being a correspondingly diverse array of mental health services. The disorders experienced by children and adolescents can become apparent in the family, the school, the pediatricians office, the social welfare agency or the courts, and the settings in which services may be provided can include any or all of these, as well as numerous others. Indeed, it has become standard practice in discussing mental health service delivery for this population to emphasize systems of care, although identifying the outlines and boundaries of such systems can itself be a daunting task. The chapters in this volume singly and collectively reflect the richness and complexity of research in this burgeoning and vitally important area and also highlight the novel conceptual and methodological approaches researchers in this field are taking in tackling its most critical issues. It focuses on the unique challenges related to mental health services for children. It examines the different settings (school, home, community, etc.) where treatment and diagnosis may take place. It reviews literature in the area and discusses the creative approaches taken by researchers.
Title from e-book title screen (viewed Oct. 8, 2007).
Includes bibliographical references.
Description based on print version record.
Keywords: Community mental health services for children; Community mental health services for teenagers; Mental health services; Child welfare; Social Science -- Sociology -- General